Insights into subunit interactions within the insect olfactory receptor complex using FRET. - German, P.F.; van der Poel, S.; Carraher, C.; Kralicek, A.V.; Newcomb, R.D. (Insect Biochemistry and Molecular Biology, 2013)
Insect olfactory receptors (ORs) are a novel family of ligand-gated cation channels that can respond to volatile organic compounds at low concentrations. They are involved in the detection of odorants associated with mate recognition, food localisation and predator avoidance. These receptors form a complex that is currently thought to contain at least two subunit members: the non-canonical Orco ion channel subunit and a ligand-binding receptor subunit. The integral membrane proteins SNMP1 and 2 are also associated with olfactory function, with SNMP1 required for cis-vaccinyl acetate reception in Drosophila melanogaster. In order to investigate protein-protein interactions among these membrane proteins we measured intermolecular Förster/Fluorescence Resonance Energy Transfer (FRET) in live insect cells by acceptor photobleaching. Fusion proteins containing Cyan Fluorescent Protein or Yellow Fluorescent Protein were produced using baculovirus-mediated expression in High Five cells. The majority of the recombinant products were of the expected size for the fusion proteins and located within intracellular membranes. We were able to show FRET efficiencies providing evidence for homomeric and heteromeric interactions of the ligand-binding OR, Or22a, and Orco (Or22a-Or22a, Or22a-Orco, Orco-Orco). There was no evidence for an interaction between SNMP1 and Orco or between SNMP2 and Orco or Or22a. However, fusion proteins of SNMP1 and Or22a did show an interaction by FRET, suggesting SNMP1 may interact with at least some insect olfactory receptor complexes. In summary, this study supports previously observed homomeric and heteromeric interactions between Orco and the ligand-binding OR, Or22a, and identifies a novel interaction between Or22a and SNMP1.